PENGARUH KECOCOKAN KONTINJEN ANTARA STRATEGI BISNIS DENGAN KETIDAKPASTIAN LINGKUNGAN TERHADAP PENGHINDARAN PAJAK - Putri, Rizkya Kusuma; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect contingent fit between business strategies and environmental uncertainty on tax avoidance disclosure in Indonesian companies. The population in this study were all companies registered in Indonesia Stock Exchange for year 2016-2019. The sampling method used in this study was purposive sampling. Samples obtained were 27 companies for the four years obtained (2016-2019). The analytical method used in this study was multinominal logistic regression and panel data regression. The result of this study indicate that in highly uncertain environment, the contingent fit level of defender strategy is higher than analyzer strategies. This study also indicate that the contingent fit between prospector strategy and environmentak uncertainty has a positive effect on tax avoidance, and this effect is higher than for the two other strategies. Moreover, the fit level of defender strategy to environmental uncertainty affects tax avoidance. Meanwhile environmental uncertainty positively affects tax avoidance.